Bacillus halotolerans KKD1 induces physiological, metabolic and molecular reprogramming in wheat under saline condition - Wu, Xiaohui; Fan, Yaning; Wang, Ruoyi; Zhao, Qian; Ali, Qurban; Wu, Huijun; Gu, Qin; Borriss, Rainer; Xie, Yongli; Gao, Xuewen (Frontiers in Plant Science, 2022)
Salt stress decreases plant growth and is a major threat to crop yields worldwide. The present study aimed to alleviate salt stress in plants by inoculation with halophilic plant growth–promoting rhizobacteria (PGPR) isolated from an extreme environment in the Qinghai–Tibetan Plateau. Wheat plants inoculated with Bacillus halotolerans KKD1 showed increased seedling morphological parameters and physiological indexes. The expression of wheat genes directly involved in plant growth was upregulated in the presence of KKD1, as shown by real-time quantitative PCR analysis. The metabolism of phytohormones, such as 6-benzylaminopurine and gibberellic acid were also enhanced. Mining of the KKD1 genome corroborated its potential plant growth promotion and biocontrol properties. Moreover, KKD1 was able to support plant growth under salt stress by inducing a stress response in wheat by modulating phytohormone levels, regulating lipid peroxidation, accumulating betaine, and excluding Na+. In addition, KKD1 positively affected the soil nitrogen content, soil phosphorus content and soil pH. Our findings indicated that KKD1 is a promising candidate for encouraging wheat plant growth under saline conditions.